THE RELATIONSHIP OF PREGNANT WOMEN'S KNOWLEDGE ABOUT THE IMPORTANCE OF ULTRASOUND EXAMINATION WITH FETAL HAZARD EVENTS IN DR PIRNGADI HOSPITAL, MEDAN CITY IN 2023 - Bakara, Rizky Andriani (Cattleya Darmaya Fortuna, 2024)
Ultrasonography (USG) is an imaging modality using high-frequency sound waves that produces cross-sectional images of the fetus. The purpose of this study was to analyze the relationship between the level of knowledge of pregnant women about the importance of ultrasound and the incidence of fetal harm at Dr Pirngadi Hospital, Medan City. Analytical survey research methods. A sample of 50 people using the Random Sampling technique using the slovin formula. The results showed that the majority of mothers aged 20-35 years with adequate knowledge category were 19 people (59.4%), education level, the majority of mothers with high school education were in the sufficient category, 12 people (57.1%), sources of information, the majority of mothers 14 people (66.7%) obtained information from electronic media with sufficient category, and based on economic status, the majority of mothers with middle economic status with sufficient category were 14 people (66.7%). The results of the Chi-Square test were all below 0.05 (0.044, 0.014, 0.013, and 0.008) <0.05, so there is a relationship between variables. It is hoped that the cooperation of health workers, midwives, cadres and pregnant women will carry out ANC examinations properly and carry out ultrasound as recommended.